Influence of Rhizobacteria and Seed Pruning on Plant Growth and Results Red Chili (Capsicum annum L.) - Zahanis, Zahanis; Fatimah, Fatimah; Devi, Devi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
This study aims to determine the effect of rhizobacteria and seed pruning on the growth and yield of red chilies. This research has been carried out in the Malvinas Delta permanent nursery, Padang Watershed Management Agency (BPDAS). This experiment used a factorial completely randomized design with 2 factors. The first factor was pruning the seeds, namely: without pruning, trimming at 21 days after sowing, trimming at 30 days after sowing. The second factor is the provision of rhizobacteria which consists of: without rhizobacteria and given rhizobacteria. The observations made in the experiment were plant height, number of primary branches, age of flowering, age at first harvest, length of fruit, number of fruit planted, and weight of fruit planted. The results of the experiment showed a significant interaction between pruning seeds and giving rhizobacteria to the growth and yield of red chilies at the plant height and number of branches. The influence of rhizobacteria on the growth and yield of red chilies on the parameters of the age of flowering, number of fruit planted, and fruit weight of the plant with a yield of 156.70 g/plant.